Cosmological constraints on the Undulant Universe - Lan, Tian; Gong, Yan; Wan, Hao-Yi; Zhang, Tong-Jie (Research in astronomy and astrophysics, 2010)
We use the redshift Hubble parameter H（z） data derived from relative galaxy ages, distant type Ia supernovae （SNe Ia）, the Baryonic Acoustic Oscillation （BAO） peak, and the Cosmic Microwave Background （CMB） shift parameter data, to constrain cosmological parameters in the Undulant Universe. We marginalize the like- lihood functions over h by integrating the probability density 19 ∝ e-x^2/2. By using a Markov Chain Monte Carlo （MCMC） technique, we obtain the best fitting results and give the confidence regions in the b - Ωm0 plane. Then we compare their constraints. Our results show that the H（z） data play a similar role with the SNe Ia data in cosmological study. By presenting the independent and joint constraints, we find that the BAO and CMB data play very important roles in breaking the degeneracy compared with the H（z） and SNe Ia data alone. Combined with the BAO or CMB data, one can remarkably improve the constraints. The SNe Ia data sets constrain Ωm0 much tighter than the H（z） data sets, but the H（z） data sets constrain b much tighter than the SNe Ia data sets. All these results show that the Undulant Universe approaches the ACDM model. We expect more H（z） data to constrain cosmological parameters in the future.